Tropical Meridional Overturning Circulation Observed by Subsurface Moorings in the Western Pacific - Song, Lina (Sci Rep, 2018)
Meridional ocean current in the northwestern Pacific was documented by seven subsurface moorings deployed at 142°E during August 2014-October 2015. A sandwich structure of the tropical meridional overturning circulation (TMOC) was revealed between 0–6°N that consists of a surface northward flow (0–80 m), a thermocline southward flow (80–260 m; 22.6–26.5 σ(θ)), and a subthermocline northward flow (260–500 m; 26.5–26.9 σ(θ)). Based on mooring data, along with satellite and reanalysis data, prominent seasonal-to-interannual variations were observed in all three layers, and the equatorial zonal winds were found to be a dominant cause of the variations. The TMOC is generally stronger in boreal winter and weaker in summer. During 2014–2015, the TMOC was greatly weakened by westerly wind anomalies associated with the El Niño condition. Further analysis suggests that the TMOC can affect equatorial surface temperature in the western Pacific through anomalous upwelling/downwelling and likely plays a vital role in the El Niño-Southern Oscillation (ENSO).